DESAIN DAN IMPLEMENTASI SISTEM VIRTUAL OFFICE - Bonok, Zainudin (Sainstek, 2009)
The aim of the study was to design a system that can increase the virtual office service system and evaluation parameter and its application as a source of information that can be used easily and rafidly. The study was conducted at the chamber of trade and Industry office in Makassar, South Sulawesi province. The study was conducted by developing the PHP programming software and AJAX programming technology. The hardware used was laptop or personal computer and the PHP programming software and AJAX programming technology. The results of the study indicate that the implementation of virtual office can renew the process of office work by working system to working target and can be used rapidly and easily when it is supported by adequate infrastructure network and can improve working productivity. The chamber of commerce and industry is the first user for 720 hours in which 90 % of the respondents state that their working productivity increases a great deal and the office work can be done without the limit of time, distance, and traffic jam.